Normalized parameters of a magnetoresistive sensor in bridge circuits - Penin Alexander A. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2021)
Magnetoresistive sensors are considered as part of bridge circuits for measuring magnetic field strength and electric current value. Normalized or relative expressions are introduced to change the resistance of the sensor and the measured bridge voltage to increase the information content of the regime to provide the possibility of comparing the regimes of different sensors. To justify these expressions, a geometric interpretation of the bridge regimes, which leads to hyperbolic straight line geometry and a cross ratio of four points, is given. Upon a change in the sensor resistance, the bridge regime is quantified by the value of the cross ratio of four samples (three characteristic values and the current or real value) of voltage and resistance. The cross ratio, as a dimensionless value, is taken as a normalized expression for the bridge voltage and sensor resistance. Moreover, the cross ratio value is an invariant for voltage and resistance. The proposed approach considers linear and nonlinear dependences of measured voltage on sensor resistance from general positions.Se analizează utilizarea senzorilor magnetorezistivi ca parte componentă a circuitelor în punte pentru măsurarea intensității câmpului magnetic și a curentului electric. Pentru a spori capacitatea informativă a regimului de lucru, a oferi posibilitatea de a compara regimurile diferitor senzori, sunt introduse expresii normalizate sau relative pentru schimbarea rezistenței senzorului și a tensiunii măsurate a punții. Pentru a fundamenta aceste expresii, se utilizează interpretarea geometrică a regimurilor de punte, ceea ce duce la geometria hiperbolică a liniei drepte și la raportul complex a patru puncte. Atunci când rezistența senzorului se schimbă, regimul de punte este determinat cantitativ de valoarea raportului complex a patru eșantioane (trei valori caracteristice și valoarea actuală) a tensiunii și rezistenței. Raportul complex, ca mărime adimensională, este luat ca expresie normalizată pentru tensiunea punții și rezistența senzorului. În plus, valoarea raportului complex este un invariant pentru tensiune și rezistență. Abordarea propusă ia în considerare, din punct de vedere general, dependențele liniare și neliniare ale tensiunii măsurate de rezistența senzorului.